PENGARUH LITERASI KEUANGAN, PERSEPSI KEMANFAATAN, PERSEPSI KEMUDAHAN PENGGUNAAN, SIKAP PENGUNAAN TEKNOLOGI DAN RISIKO TERHADAP KEPUTUSAN PENGGUNAAN QUICK RESPONS INDONESIA STANDARD (QRIS): UMKM Kota Balikpapan - Fitriasari, Pipin (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2025)
This study aims to determine the influence of financial literacy, perceived usefulness, ease of use, attitude towards technology use, and risk. This research is a descriptive quantitative study. The objects used in this study are SMEs fostered by the Department of Cooperatives and Industry in Balikpapan City. The sampling technique used is non-probability sampling with a sample of 125 respondents. The results of this study indicate that the variables of financial literacy, perceived usefulness, ease of use, and risk significantly influence the decision to use QRIS, while the attitude towards technology use does not significantly affect the decision to use QRIS. The most significant influence is financial literacy.